The Content of the Attitudes "I Am Now" and "I Am an Adult" in Adolescents with Different Characteristics of Personal Maturity - Anastasia V. Miklyaeva; Olga V. Rudykhina; Alexandra S. Tolkacheva (National Research Mordova State University, 2023)
Introduction. In the modern world, there is an expansion of the spectrum of transition trajectories to adulthood in adolescents and young people as well as the increased importance of "subjective markers of adulthood", which represent a set of qualities of a "mature personality". There is no idea about the specifics of the growing up trajectories among modern adolescents, taking into account their psychological characteristics. The purpose of the article is to investigate the quantitative and qualitative indicators of the images "I am now" and "I am an adult" in adolescents with different levels of personal maturity. Materials and Methods. The survey involved 1 097 adolescents aged between 13 - 17. The method of contrast groups by the Self-assessment Scale of personal maturity allowed to identify subgroups of adolescents with high and low levels of personal maturity. The quantitative and qualitative characteristics of the attitudes "I am now" and "I am an adult" obtained by the modified "Who am I?" technique were compared in these subgroups. Results. Regardless of the characteristics of personal maturity, adolescents include more elements in the attitudes "I am now" than in "I am an adult"; the core of both attitudes includes mainly the characteristics of the socio-demographic, formalized and individualized Self. Differences between the subgroups of adolescents with HPM and LPM include: different age dynamics of the number of elements in the attitudes "I am now" and "I am an adult" (a consistent decrease in the number of elements in adolescents with HPM against an absence of significant changes in the sample of their peers with LPM), as well as a more significant contribution of the characteristics of social-role functioning in attitudes "I am now" and "I am an adult" in adolescents with HPM. Discussion and Conclusion. The research contributes to the understanding of the psychological characteristics of modern adolescents who are at the stage of transition to adulthood. The results will be useful for the practice of psychological and pedagogical support of growing up and psychological counseling on personal self-determination in adolescence.